Literatur Review: Analisis Efisiensi, Efektivitas, Dan Kontribusi Pajak Daerah Dan Retribusi Daerah Terhadap Peningkatan Pendapatan Asli Daerah - Aminatus Sofia (Journal of Creative Student Research, 2023)
The type of research used in this study is Literature Review. This study uses data from journals that are available in full text form. The data source is traced and retrieved from Google Scholar. The subject of this research is Efficiency, Effectiveness and Contribution of Regional Taxes and Regional Levies to Increasing Regional Original Income, while the object is the article. From several articles that have been researched, they discuss the efficiency, effectiveness, and contribution of local taxes and regional levies. The study found that the level of effectiveness of local taxes was effective, very effective, or even ineffective. Based on research using the effectiveness ratio, the level of Regional Tax collection is stated to be very effective even though it tends to fluctuate (up and down). Based on the efficiency ratio, the level of Regional Tax collection tends to rise and fall (fluctuate) per year but overall there is a decrease in costs and taxes generated.